Use of the N-alkanes to Estimate Intake, Apparent Digestibility and Diet Composition in Sheep Grazing on Stipa breviflora Desert Steppe - Hong-lian HU; Yong-zhi LIU; Ya-kui LI; De-xun LU; Min GAO (Journal of Integrative Agriculture, 2014)
The application of n-alkane as markers to estimate herbage intake, apparent digestibility and species composition of diet consumed by grazing sheep was studied. Six local Mongolian sheep were used to determine dry matter (DM) intake, apparent DM digestibility and species composition of diet during summer, autumn and winter. Animals were orally dosed twice daily with n-alkane gelatin capsules containing 60 mg C32-alkane as an external marker. Diet composition was estimated by comparing the odd-chain n-alkanes pattern profile (C27-C31) of the consumed plant species with the n-alkanes fecal concentrations of grazing animals, using a non-negative least squares algorithm called EATWHAT software package. The alkane pair C32:C33 and C33 alkane were used to estimate DM intake and diet apparent DM digestibility, respectively. The results showed that daily dry matter intake of the sheep were 1.77, 1.61 and 1.18 kg d−1 in summer, autumn and winter, respectively. Apparent DM digestibility, crude protein (CP), metabolizable energy (ME) and neutral detergent fiber (NDF) intake of diet consumed by sheep decreased significantly (P<0.01) from summer to winter, with no evident changes in ADF and ADL intake. Diet composition indicated Artemisia frigida Willd was the most dominant diet component, contributed 79.68, 68.12 and 86.26% of sheep's diets in summer, autumn and winter, respectively. Cleistogenes songorica Ohwi and Convolvulus ammannii Desr were the important components of the diet. Although Stipa breviflora Griseb is one of the main plant species in the study area, the sheep rarely choosed it. The study indicated that CP and ME in diet consumed by sheep were deficient in winter. Therefore, appropriate supplementation strategies should be indispensable during this period.